Dilated cardiomyopathy and myocarditis: a clinical case - O.V. Onyshchenko; D.V. Riabenko; O.A. Yepanchintseva (Кардіохірургія та інтервенційна кардіологія)
The article describes a clinical case of a combination of myocarditis and hereditary dilated cardiomyopathy. In a 40-year-old man cardiomegaly and HF, which occurred for the first time, were initially associated with an inflammatory process in the myocardium. Further genetic examinations showed that pathological processes in the myocardium are also associated with a pathogenic mutation in the FLNC gene and a mutation in the TNT gene. The myocarditis that developed on the background of family (hereditary) dilated cardiomyopathy. However, despite the positive effect of the treatment of myocarditis and contemporary drug therapy, the progression of the pathological process in the myocardium was noted. This clinical case emphasizes the importance of a complete diagnostic examination with the use of genetic testing in certain cases.